2015
DOI: 10.4155/fmc.15.41
|View full text |Cite
|
Sign up to set email alerts
|

Pyranopyrazolotacrines as Nonneurotoxic, Aβ-Anti-Aggregating and Neuroprotective Agents for Alzheimer's Disease

Abstract: Aim: Due to the complex nature of Alzheimer's disease, there is a renewed search for multipotent, nonhepatotoxic tacrines. Results: This paper describes the synthesis and in vitro biological evaluation of eight new racemic 3-methyl-4-aryl-2,4,6,7,8,9-hexahydropyrazolo[4′,3′:5,6]pyrano[2,3-b]quinolin-5-amines (pyranopyrazolotacrines, PPT) as nonhepatotoxic multipotent tacrine analogs. Among these compounds, PPT4 is the less hepatotoxic in the cell viability assay on HepG2 cells, showing a good neuroprotective e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Alzheimer’s disease is a neurodegenerative, progressive disorder of central nervous system (CNS) that generally affects aged people. It is the most common cause of dementia which makes up 70% of senile dementia 1 . Today there are 47 million people living with dementia worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease is a neurodegenerative, progressive disorder of central nervous system (CNS) that generally affects aged people. It is the most common cause of dementia which makes up 70% of senile dementia 1 . Today there are 47 million people living with dementia worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Once more, no clear SAR was evident, although an electron-withdrawing group at C4′, such as nitro (94o), or an electron-donor substituent at C2′, such as methoxy (94f), seemed to afford the best inhibitory capacity. 70 A mechanism underlying the kinetic inhibition of EeAChE by 94f, the least hepatotoxic and most efficacious AChEI, was proposed, indicating that 94f behaved as a noncompetitive inhibitor. This result was confirmed by the statistical analysis of K m and V max tendencies, which clearly demonstrated a significant trend for V max to decrease, whereas K m did not exhibit a statistically significant tendency to increase.…”
Section: Account Synlettmentioning
confidence: 99%
“…These results confirmed the observed noncompetitive inhibition mechanism for the inhibition of EeAChE by these pyranopyrazolotacrines. 70 Neuroprotection investigation was carried out with the cocktail oligomycin A (10 M)/rotenone (30 M) as a toxic insult that blocks mitochondrial electron transport chain complexes I and V, thereby inducing cell death by oxidative stress in a concentration-dependent manner.…”
Section: Account Synlettmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the most effective compound 1d bearing a 3,4-dimethoxyphenyl group was more active than the reference drug tacrine and significantly protected neurons against oxidative stress, as potent as quercetin at low concentrations. A similar tacrine analogs family has been independently and almost simultaneously described by Marco-Contelles’ team [131].…”
Section: New Multifunctional Analogues and Hybrids Of Tacrinementioning
confidence: 99%